Evaluasi Kinerja Sistem Peminjaman Buku di Perpustakaan SMP Santo Leo II dengan Pendekatan Pieces - Febrianto Febrianto; I Ketut Sudaryana; Sandri Sagitarius Sarumaha (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
This study evaluates the Performance of the book lending system at the SMP Santo Leo II Library using the PIECES framework. The lending process is still fully manual, which affects the accuracy, speed, and Efficiency of Services. Data were collected through observation, interviews, documentation, and questionnaires involving 45 respondents. The questionnaire results show that the overall Performance of the system remains low: Performance (1.96), Information (1.79), Economy (1.90), Control (1.75), Efficiency (2.01), and Service (1.90). These scores fall within the low to very low categories. The findings indicate frequent inconsistencies in book availability data, slow transaction handling during peak hours, limited Control and data security, and inefficient workflows due to the absence of a computerized system. Users also experience difficulties in locating books and delays in returning them because no structured reminder system exists. The study concludes that the existing manual system is no longer adequate to support library operations, and a computerized library Information system is urgently needed to improve accuracy, Service speed, and overall operational Efficiency.